The mobile phone: technological device for the development of communicative competences - Pineda Díaz, Diana Carolina; Rivera Guío, Ximena Gisele; Murcia Pardo, Sandra Milena (Universidad Pedagógica y Tecnológica de Colombia, 2019)
This article of reflection derives from the research “oral communicative competence through the use of cell phones”, whose objective was to identify how the use of the mobile device affects the improvement of the oral communicative competence of ninth grade students in the Educational Institution of Nobsa (Colombia) , through the analysis and interpretation of how technology has influenced the quality of education, its contributions to it and the advances that have been made in the development of cognitive skills and communication skills. From a theoretical basis, it seeks to define the concepts that support the research process that has a critical social approach generating a change of thought in the educational context. Likewise, the work is part of the Educational Research-Action. Consequently, the impacts achieved are presented with a proposal that used the cell phone as a pedagogical tool, in workshops that managed to enhance some of the skills needed to achieve an adequate oral communication competence, and how an environment was created where students with motivation, Collaborative work and innovation took advantage of the pedagogical features that the device can offer by being multifunctional, affordable and portable.